2005
DOI: 10.1128/aac.49.1.148-152.2005
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Oritavancin in Plasma and Skin Blister Fluid following Administration of a 200-Milligram Dose for 3 Days or a Single 800-Milligram Dose

Abstract: Oritavancin is a novel glycopeptide currently being developed for the treatment of complicated skin and skin structure infections (cSSSI), including those caused by multidrug resistant gram-positive pathogens. The disposition of oritavancin in skin structures was investigated using a cantharide-induced blister fluid model. Seventeen healthy male subjects received oritavancin, but only 16 subjects were evaluated after one subject discontinued study drug. Each subject (eight per dose group) received 200 mg of or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
48
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 8 publications
0
48
0
Order By: Relevance
“…dose of oritavancin 24 h before aerosol challenge underscores the extended half-life of this drug (5,15,27,28). Furthermore, this finding suggests that oritavancin may concentrate in those cellular compartments where spores may germinate in the early stages of infection (24,26).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…dose of oritavancin 24 h before aerosol challenge underscores the extended half-life of this drug (5,15,27,28). Furthermore, this finding suggests that oritavancin may concentrate in those cellular compartments where spores may germinate in the early stages of infection (24,26).…”
Section: Discussionmentioning
confidence: 85%
“…For comparison, an oritavancin fAUC 0-24 h of 167 g ⅐ h/ml is predicted in human plasma following a single 800-mg i.v. dose (15), with a human serum protein binding value of 85% (5). Thus, total drug exposures that provide maximal or near-maximal single-dose efficacy in the mouse inhalational anthrax model are clinically relevant.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous phase 1, 2, and 3 studies have been conducted evaluating oritavancin in both healthy subjects and infected patients with cSSSI or Staphylococcus aureus bacteremia (3,8,12). It has been administered as either single-or multiple-dose intravenous (i.v.)…”
mentioning
confidence: 99%
“…infusions in fixed doses ranging from 100 to 800 mg or as weight-based doses ranging from 0.02 to 10 mg/kg of body weight. Pharmacokinetic (PK) studies have shown that oritavancin displays linear PKs for weightbased or fixed dose ranges (3,8,12). Additionally, oritavancin was shown to be safe and well tolerated, with no clinically relevant changes in renal, hepatic, or hematological indices compared to the individual's baseline.…”
mentioning
confidence: 99%
“…Oritavancin concentrations (Table 1) were chosen to approximate the closest MIC doubling dilution to the total (protein bound plus unbound) peak (C max ) and total trough levels in plasma following administration of a 200-mg dose (6,7,13).…”
mentioning
confidence: 99%